Observasi Penerapan Model Pembelajaran Inkuiri Terbimbing pada Materi Pertumbuhan dan Perkembangan Tumbuhan untuk Meningkatkan Keterampilan Proses Sains Peserta Didik - Septia Yusuf; Ani M. Hasan; Jusna Ahmad (Postgraduate, University of Mataram, 2023)
The purpose of the study was to improve the science process skills of students who used the guided inquiry learning model on plant growth and development material. This type of research is quasi experimental in the form of Nonequivalent control group design. Population of all XII IPA classes. Samples of class XII IPA 1 (experimental) using guided inquiry learning model and class XII IPA 2 (control) with discovery learning model. Indicators of science process skills observed in this study consisted of aspects of observing, classifying, interpreting, predicting, asking questions, hypothesizing, using tools and materials, planning experiments, and communicating. The results of the study, science process skills in the experimental class the percentage is higher than the control class. In the experimental class, the aspect of observing was the highest aspect with a percentage of 88.39% while in the control class the highest aspect was the aspect of observing and asking questions with a percentage of 82.09% and 82.59%. The lowest percentage aspect is hypothesizing both experimental and control classes with a percentage of 80.36% and 58.04%. So the observation of the application of the guided inquiry learning model on plant growth and development material can improve students' science process skills. Â Â Â